Legal Protection Of Minority Shareholders Of Companies In Indonesia - Oloan Tua Partempuan; Adi Mansar (Abdurrauf Social Science, 2026)
This research offers a new approach by emphasizing the reconstruction of the decision-making mechanism in the GMS that is not only oriented towards the principle of majority vote (majority rule), but also integrates the principle of substantive justice for minority shareholders. The novelty lies in the effort to formulate a more progressive model of legal protection through the application of the principle of equitable governance, namely the balance between majority power and the protection of minority rights within the structure of a limited liability company. This situation creates an imbalance in legal standing and potentially leads to arbitrary actions by the majority shareholder. This study aims to analyze the form and effectiveness of legal protection for minority shareholders in decision-making at the General Meeting of Shareholders (GMS). Using normative juridical research methods and a statutory approach, as well as case studies, this study finds that legal protection for minority shareholders is regulated in the Limited Liability Company Law (UUPT), but its implementation still faces many obstacles. The dominance of the majority shareholder, information asymmetry, and limited law enforcement mechanisms are the main factors that reduce the effectiveness of this protection. This study recommends strengthening regulations, increasing transparency, and optimizing dispute resolution mechanisms.